2016
DOI: 10.1002/bio.3145
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic investigation of water‐soluble alloyed QDs with bovine serum albumin

Abstract: We present here a systematic investigation on the interaction between a water-soluble alloyed semiconductor quantum dot and bovine serum albumin using various spectroscopic techniques i.e. fluorescence quenching, resonance light scattering and synchronous fluorescence spectroscopy. The analysis of fluorescence spectrum and fluorescence intensity indicates that the intrinsic fluorescence of bovine serum albumin (BSA) gets quenched by both static and dynamic quenching mechanism. The Stern-Volmer quenching consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 52 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Further, we have used the following simplified Equation () to calculate the Förster distance ( R 0 ) in angstrom between Trp and QDs R0=0.211×108n4κ2QDJλ16 where n is the refractive index of the medium, κ 2 is orientation factor (2/3 for randomly oriented dipoles) and Q D is the quantum yield of the donor BSA protein (i.e. 0.118). Förster distance is the separation between the surfaces of donor and the acceptor which corresponds to separation between donor and acceptor when the energy transfer efficiency ( E T ) is equal to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we have used the following simplified Equation () to calculate the Förster distance ( R 0 ) in angstrom between Trp and QDs R0=0.211×108n4κ2QDJλ16 where n is the refractive index of the medium, κ 2 is orientation factor (2/3 for randomly oriented dipoles) and Q D is the quantum yield of the donor BSA protein (i.e. 0.118). Förster distance is the separation between the surfaces of donor and the acceptor which corresponds to separation between donor and acceptor when the energy transfer efficiency ( E T ) is equal to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Δ H o and Δ S o presented in Table were calculated by using the slope and intercept values from Figure . According to the enthalpy and entropy changes, the model of interaction between QD and biomolecules can be summarized as follows: in general (i) if Δ H o > 0 and Δ S o > 0, association processes are triggered by hydrophobic interactions between proteins and ligands; (ii) if Δ H o < 0 and Δ S o < 0 the processes are triggered by hydrogen bonding and van der Waal's forces; and (iii) Δ H o < 0 and Δ S o > 0 indicate electrostatic interaction …”
Section: Resultsmentioning
confidence: 99%
“…Thus it was concluded that hydrophobic forces play a major role in the binding interaction between BSA and QDs. Hydrophobic interactions are important for the folding of proteins because this keeps a protein alive and biologically active during the interaction …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations